Arc Interference Behavior during Twin Wire Gas Metal Arc Welding Process - Dingjian Ye; Xueming Hua; Yixiong Wu (Advances in Materials Science and Engineering)
In order to study arc interference behavior during twin wire gas metal arc welding process, the synchronous acquisition system has been established to acquire instantaneous information of arc profile including dynamic arc length variation as well as relative voltage and current signals. The results show that after trailing arc (T-arc) is added to the middle arc (M-arc) in a stable welding process, the current of M arc remains unchanged while the agitation increases; the voltage of M arc has an obvious increase; the shape of M arc changes, with increasing width, length, and area; the transfer frequency of M arc droplet increases and the droplet itself becomes smaller. The wire extension length of twin arc turns out to be shorter than that of single arc welding.